Exploring Consumer Transition to Energy-Efficient Household Appliances in Indonesia: The Mediating Role of Curiosity in a Push-Pull-Mooring Framework - Andika, Andika; Maslikhah, Maslikhah; Tampubolon, Nobel Kristian Tripandoyo; Wahyudi, Danang; Dwiwinarno, Titop; Amirullah, Malik Abd Karim (International Journal of Energy Economics and Policy, 2025)
This research is motivated by the increase in energy consumption in the Indonesian household sector, especially on the island of Java, which contributes significantly to greenhouse gas emissions. Although the government has implemented an energy-saving label policy, the adoption of energy-saving appliances still needs to be higher. The main problems identified include low consumer awareness of the long-term benefits, high perception of initial costs, and lack of effective information dissemination. This study aims to analyze the factors that affect consumer intentions in switching to energy- efficient appliances using the Push-Pull-Mooring (PPM) theory. Environmental consciousness functions as a push factor, social media, energy-saving labels, Curiosity as a pull factor, and technology compatibility as a mooring factor. A quantitative survey was conducted on 310 households in Java, and the data was analyzed using PLS-SEM. The results show that environmental consciousness and Curiosity influence consumers’ intention to switch, while technology compatibility strengthens adoption decisions. In addition, social media and energy labels directly increase consumer curiosity about energy-efficient appliances. The implications of this study include strategic recommendations for governments and marketers to increase awareness campaigns and financial incentives and leverage social media to accelerate the adoption of sustainable technologies in the household sector.